A method for preparing ultra-high performance carbon fiber
Polyacrylonitrile spinning liquid was prepared through stage temperature-controlled polymerization, and the carbonization treatment was used to solve the problems of uneven strength and unstable quality of carbon fibers in the prior art, and the engineering mass production of T1100 grade ultra-high performance carbon fibers was achieved.
Patent Information
- Application Number
- CN202410617014.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-17
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-05-17
AI Technical Summary
It is difficult to achieve the engineering mass production of ultra-high performance carbon fibers of T1100 or above in the prior art. The amount of carbon fiber wool is large, the strength is uneven, and the quality is unstable.
Using the stage-controlled polymerization method, first react at 55~65℃ for 1~3 hours, and then heat up to 65~75℃ for 13~15 hours at a temperature increase rate of 0.05~0.15℃/min to react to 65~75℃ for 13~15 hours to prepare uniform and regular polyacrylonitrile molecules chain, thereby obtaining ultra-high performance carbon fibers through carbonization.
The T1100 grade carbon fiber has excellent mechanical properties, high strength and stable mass, tensile strength reaches 6600MPa, elastic modulus reaches 324GPa, and elongation of break of 2.0%.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of carbon fiber preparation, and specifically relates to a method for preparing ultra-high performance carbon fiber. Background Art
[0002] Carbon fiber (CF) is a new type of fiber material with high strength and high modulus fiber with a carbon content of more than 95%. It is a microcrystalline graphite material obtained by stacking organic fibers such as flake graphite microcrystals along the axial direction of the fiber and undergoing carbonization and graphitization treatment. Carbon fiber is "soft on the outside and hard on the inside". It is lighter than metal aluminum, but stronger than steel. It also has the characteristics of corrosion resistance and high modulus. It is an important material in national defense, military industry and civilian use. It not only has the inherent intrinsic properties of carbon materials, but also has the softness and processability of textile fibers. It is a new generation of reinforcing fiber. With the continuous development of high-end manufacturing, the performance requirements for carbon fiber are getting higher and higher.
[0003] Since the beginning of the 21st century, the engineering production of T300-T800 grades has been accelerating, but the existing technology has a large amount of carbon fiber hair, uneven strength, and unstable quality, and it is still impossible to achieve engineering mass production of ultra-high performance carbon fiber of T1100 grade and above. Summary of the invention
[0004] In view of the problems existing in the prior art, the present invention aims to provide a method for preparing ultra-high performance carbon fiber. The preparation method comprises:
[0005] First, a polyacrylonitrile spinning solution is prepared, then a polyacrylonitrile precursor is prepared, and then the polyacrylonitrile precursor is carbonized to obtain the carbon fiber.
[0006] The preparation method of the polyacrylonitrile spinning solution comprises:
[0007] After acrylonitrile, itaconic acid, solvent and initiator are mixed and a molecular weight regulator is added, the mixture is first reacted at 55-65°C for 1-3 hours in the first stage, and then the temperature is increased to 65-75°C for 13-15 hours in the second stage at a heating rate of 0.05-0.15°C / min; after the monomer is removed, the polyacrylonitrile spinning solution is obtained after concentration, ammoniation and filtration.
[0008] Preferably, the heating rate from the first stage to the second stage is 0.083°C / min.
[0009] Preferably, the polyacrylonitrile spinning solution comprises:
[0010] Acrylonitrile 12~19 parts
[0011] Itaconic acid 0.5~1.5 parts
[0012] 30~60 parts of solvent
[0013] 0.6~1.9 parts of initiator, and
[0014] Molecular weight regulator 1~1.5 parts.
[0015] The solvent is divided into two parts, namely a first solvent and a second solvent.
[0016] Preferably, the method for preparing the polyacrylonitrile spinning solution further comprises:
[0017] First, acrylonitrile and itaconic acid are dissolved in a first solvent, filtered, and then transferred to a polymerization kettle, wherein the mass ratio of acrylonitrile to itaconic acid is 10-15:1; the mass ratio of acrylonitrile and itaconic acid to the first solvent is 1:1-2;
[0018] Then, the initiator is dissolved in the second solvent, filtered, and transferred to a polymerization kettle, wherein the mass ratio of the initiator to the second solvent is 1:14-15;
[0019] Then, a molecular weight regulator was added to start the polymerization reaction, wherein the mass ratio of the molecular weight regulator to acrylonitrile was 7:100.
[0020] Preferably, the solvent includes dimethyl sulfoxide, the initiator includes azobisisobutyronitrile, and the molecular weight regulator includes one or more of 2,2'-dicyandisulfide, succinyl diamide, ethylene glycol formate or tris(2-benzimidazolyl)silane.
[0021] Preferably, the monomer removal step is carried out in a monomer removal tower, and the pressure of the monomer removal tower is 0.001-0.002 MPa; the concentration is carried out in a concentration tower, and the pressure of the concentration tower is 0.0004-0.00065 MPa.
[0022] Preferably, the polyacrylonitrile spinning solution has a temperature of 25-40° C., a rotational viscosity of 730-780 P, an intrinsic viscosity of 1.8-1.9 dL / g, and a solid content of 18.9%-19.5%.
[0023] Preferably, the method for preparing polyacrylonitrile precursor comprises:
[0024] After the spinning solution is spun by the spinneret, it first passes through an air layer and then passes through a coagulation bath to form primary fibers. The primary fibers are then washed, oiled, dried, and steam-stretched to obtain polyacrylonitrile precursor fibers.
[0025] The oiling step is carried out in an aqueous solution of silicon carbide and silicone oil, wherein the concentration of the silicon carbide is 0.08% to 0.12% of the aqueous solution, and the concentration of the silicone oil is 2.5% to 3.5% of the aqueous solution.
[0026] Preferably, the air layer height is 3-5 mm; the coagulation bath is a dimethyl sulfoxide aqueous solution with a concentration of 25%-30% and a temperature of 3-5°C; the water washing process is alternating low-temperature water washing in a cold tank and a hot tank at 40-50°C, with a temperature difference of 2-10°C between the cold tank and the hot tank, and high-temperature water washing at 60-70°C, and the total water washing stretching multiple is 1-2 times; the steam stretching steam pressure is 1.0-1.6 MP, and the steam stretching multiple is 3.6-4.3 times.
[0027] Preferably, the method for carbonizing polyacrylonitrile precursor comprises:
[0028] First, the carbon fiber precursor is pre-oxidized, then subjected to low-temperature carbonization and high-temperature carbonization in sequence, surface treated and then washed, and then sized and dried to obtain ultra-high performance carbon fiber.
[0029] Preferably, the pre-oxidation temperature is 225~242°C, the pre-oxidation time is 70~90 min, and the drafting ratio is 0.92~0.94 times; the low-temperature carbonization temperature is 550~700°C, and the drafting ratio is 0.93~0.95 times; the high-temperature carbonization temperature is 1200~1800°C, and the drafting ratio is 0.95~0.97 times; the conductivity of the surface treatment liquid is 8.0~9.5ms / cm, and the drafting ratio is 0.97~0.99 times; the sizing agent concentration is 1.97%~2.03%, the sizing agent content is 0.8%~1.4%, the drying temperature is 180~220°C, and the drafting ratio is 0.995~1.005 times.
[0030] The beneficial effects of the present invention include:
[0031] The present invention adopts a stage temperature-controlled polymerization method, first reacts at 55-65°C for 1-3h, and then heats to 65-75°C at a heating rate of 0.05-0.15°C / min for 13-15h. The temperature range of 55-65°C in the first stage and 65-75°C in the second stage is used to finely control the growth and structural arrangement of the polymer chain to obtain a uniform and regular polyacrylonitrile molecular chain. The heating rate is controlled within the range of 0.05-0.15°C / min, which can promote the uniform structure of the polymer chain and avoid the inhomogeneity of the local structure, thereby improving the uniformity and stability of the carbon fiber. The reaction time is controlled to be 1-3h in the first stage and 13-15h in the second stage to ensure that a narrow molecular weight distribution is obtained on the basis of the maximum conversion rate. The T1100 grade carbon fiber obtained by this method has excellent mechanical properties, high strength and stable quality, a tensile strength of 6600MPa, an elastic modulus of 324GPa, and an elongation at break of 2.0%. DETAILED DESCRIPTION
[0032] Ultra-high performance carbon fiber specifically refers to T1100 grade carbon fiber. In the preparation process of ultra-high performance carbon fiber, how to obtain high-quality polyacrylonitrile carbon fiber precursor is the basis for preparing ultra-high performance polyacrylonitrile carbon fiber, and the key to obtaining high-quality polyacrylonitrile carbon fiber precursor is to prepare polyacrylonitrile spinning solution with uniform chain structure and narrow molecular weight distribution.
[0033] Based on the above, the present invention provides a method for preparing ultra-high performance carbon fiber, the preparation method comprising:
[0034] First, a polyacrylonitrile spinning solution is prepared, then a polyacrylonitrile precursor is prepared, and then the polyacrylonitrile precursor is carbonized to obtain the carbon fiber.
[0035] The preparation method of the polyacrylonitrile spinning solution comprises:
[0036] After acrylonitrile, itaconic acid, solvent and initiator are mixed, molecular weight regulator is added, and the mixture is first reacted at 55-65°C for 1-3h in the first stage, and then heated to 65-75°C for 13-15h in the second stage at a heating rate of 0.05-0.15°C / min. After the monomer is removed, the polyacrylonitrile spinning solution is obtained after concentration, ammoniation and filtration.
[0037] The polymerization reaction is controlled in the temperature range of 55~65℃ in the first stage and 65~75℃ in the second stage to finely control the polymerization reaction rate and prevent uncontrollable factors such as local overheating and uneven reaction mixture caused by too fast reaction. The polymerization reaction in this temperature range can more effectively control the growth and structural arrangement of the polymer chain, making the polyacrylonitrile molecular chain more regular and uniform, and can also reduce the formation of gel particles in the polymer, and reduce the occurrence of side reactions such as crosslinking or branching that affect the solubility and spinning performance of the polymer. The heating rate is controlled in the range of 0.05~0.15℃ / min, which can promote the uniform structure of the polymer chain and improve the uniformity and stability of the carbon fiber. The reaction time is controlled in the first stage of 1~3h and the second stage of 13~15h to ensure that on the basis of the maximum conversion rate, a narrow molecular weight distribution is obtained, the fiber structure is uniform and regular, the molecular chain breakage damage is reduced, and the strength and mechanical properties of the carbon fiber are improved.
[0038] In the present invention, the temperature of the first stage is, for example, 55°C, 56°C, 57°C, 58°C, 59°C, 60°C, 61°C, 62°C, 63°C, 64°C or 65°C; the reaction time of the first stage is, for example, 1h, 1.5h, 2h, 2.5h or 3h; the temperature of the second stage is, for example, 65°C, 66°C, 67°C, 68°C, 69°C, 70°C, 71°C, 72°C, 73°C, 74°C or 75°C; the reaction time of the second stage is, for example, 13h, 13.5h, 14h, 14.5h or 15h;
[0039] The heating rate is, for example, 0.05°C / min, 0.06°C / min, 0.07°C / min, 0.08°C / min, 0.09°C / min, 0.10°C / min, 0.11°C / min, 0.12°C / min, 0.13°C / min, 0.14°C / min or 0.15°C / min.
[0040] Preferably, the temperature of the first stage is 60° C., and the reaction time of the first stage is 2 h.
[0041] Preferably, the temperature of the second stage is 70° C., and the reaction time of the second stage is 14 h.
[0042] Preferably, the heating rate from the first stage to the second stage is 0.083°C / min.
[0043] In a preferred embodiment of the present invention, the polyacrylonitrile spinning solution comprises the following raw materials in parts by weight:
[0044] Acrylonitrile 12~19 parts
[0045] Itaconic acid 0.5~1.5 parts
[0046] 30~60 parts of solvent
[0047] 0.6~1.9 parts of initiator, and
[0048] Molecular weight regulator 1~1.5 parts.
[0049] The solvent is divided into two parts, namely a first solvent and a second solvent.
[0050] In the present invention, the mass fraction of acrylonitrile is, for example, 12 parts, 13 parts, 14 parts, 15 parts, 16 parts, 17 parts, 18 parts or 19 parts.
[0051] In the present invention, the mass fraction of itaconic acid is, for example, 0.5 parts, 0.6 parts, 0.7 parts, 0.8 parts, 0.9 parts, 1.0 parts, 1.1 parts, 1.2 parts, 1.3 parts, 1.4 parts or 1.5 parts.
[0052] In the present invention, the mass fraction of the solvent is, for example, 30 parts, 35 parts, 40 parts, 45 parts, 50 parts, 55 parts or 60 parts.
[0053] In the present invention, the mass fraction of the initiator is, for example, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8 or 1.9 parts.
[0054] In the present invention, the mass fraction of the molecular weight regulator is, for example, 1.0 parts, 1.1 parts, 1.2 parts, 1.3 parts, 1.4 parts or 1.5 parts.
[0055] In a preferred embodiment of the present invention, the method for preparing the polyacrylonitrile spinning solution further comprises:
[0056] First, acrylonitrile and itaconic acid are dissolved in the first solvent, filtered, and then transferred to a polymerization kettle. The mass ratio of acrylonitrile to itaconic acid is 10-15:1; the mass ratio of acrylonitrile and itaconic acid to the first solvent is 1:1-2.
[0057] The mass ratio of acrylonitrile to itaconic acid is, for example, 10:1, 11:1, 12:1, 13:1, 14:1 or 15:1; the mass ratio of acrylonitrile to itaconic acid to the first solvent is, for example, 1:1.0, 1:1.1, 1:1.2, 1:1.3, 1:1.4, 1:1.5, 1:1.6, 1:1.7, 1:1.8, 1:1.9 or 1:2.0.
[0058] Then, the initiator is dissolved in the second solvent, filtered, and then transferred to a polymerization kettle, and the mass ratio of the initiator to the second solvent is 1:14-15.
[0059] In the present invention, the mass ratio of the initiator to the second solvent is 1:14.0, 1:14.1, 1:14.2, 1:14.3, 1:14.4, 1:14.5, 1:14.6, 1:14.7, 1:14.8, 1:14.9 or 1:15.0.
[0060] Then, a molecular weight regulator was added to start the polymerization reaction, wherein the mass ratio of the molecular weight regulator to acrylonitrile was 7:100.
[0061] In the present invention, the solvent includes dimethyl sulfoxide, the initiator includes azobisisobutyronitrile, and the molecular weight regulator includes one or more of 2,2'-dicyandisulfide, succinyl diamide, ethylene glycol formate or tris(2-benzimidazolyl)silane.
[0062] In a preferred embodiment of the present invention, the molecular weight regulator is, for example, 2,2'-dicyandisulfide, succinyl diamide, ethylene glycol formate, tris(2-benzimidazolyl)silane, 2,2'-dicyandisulfide and succinyl diamide, or a combination of 2,2'-dicyandisulfide and ethylene glycol formate.
[0063] Preferably, the molecular weight regulator comprises 2,2'-dicyanodisulfide.
[0064] In a preferred embodiment of the present invention, the monomer removal is carried out in a monomer removal tower, and the pressure of the monomer removal tower is 0.001-0.002 MPa; the concentration is carried out in a concentration tower, and the pressure of the concentration tower is 0.0004-0.00065 MPa.
[0065] In a preferred embodiment of the present invention, the method for preparing the polyacrylonitrile spinning solution is specifically as follows:
[0066] Dissolve 12-19 parts of acrylonitrile, 0.5-1.5 parts of itaconic acid and the first part of the solvent at 40°C, filter and transfer to a polymerization kettle;
[0067] Then, 0.6-1.9 parts of the initiator and the second part of the solvent were dissolved at 40°C, filtered, and transferred to the polymerization kettle;
[0068] Then, a molecular weight regulator is added to carry out polymerization reaction.
[0069] During the polymerization reaction, the temperature of the polymerization kettle is controlled at 55~65°C in the first stage. After reacting for 1~3 hours, the temperature is increased to 65~75°C at a heating rate of 0.05~0.15°C / min for the second stage reaction, and the temperature is kept for 13~15 hours.
[0070] After the reaction is completed, the polymer solution is transferred to a stripping tower through a pump to remove acrylonitrile monomer, and the absolute pressure in the stripping tower is controlled to be 0.001~0.002MPa; then it is transferred to a concentration tower for concentration, and the absolute pressure in the concentration tower is controlled to be 0.0004~0.00065MPa; then 5%~10% ammonia water is added for amination for 1~2h, and then the polyacrylonitrile spinning solution is obtained after 3-stage filtration.
[0071] In a preferred embodiment of the present invention, the polyacrylonitrile spinning solution has a temperature of 25-40° C., a rotational viscosity of 730-780 P, an intrinsic viscosity of 1.8-1.9 dL / g, and a solid content of 18.9%-19.5%.
[0072] In the present invention, the spinning solution needs to maintain a suitable temperature range. Too low a temperature will increase the viscosity of the spinning solution, making it difficult to transport the solution through a pipeline, which will seriously affect the production efficiency. Too high a temperature may cause changes in the dimensional structure and oxidation damage to the fiber surface, reducing the performance and stability of the fiber, thereby affecting the physical properties and mechanical properties of the carbon fiber. The spinning solution temperature is, for example, 25°C, 26°C, 27°C, 28°C, 29°C, 30°C, 31°C, 32°C, 33°C, 34°C, 35°C, 36°C, 37°C, 38°C, 39°C or 40°C.
[0073] In a preferred embodiment of the present invention, the method for preparing polyacrylonitrile precursor comprises:
[0074] After the spinning solution is spun by the spinneret, it first passes through an air layer and then passes through a coagulation bath to form primary fibers. The primary fibers are then washed, oiled, dried, and steam-stretched to obtain polyacrylonitrile precursor fibers.
[0075] The oiling step is carried out in an aqueous solution of silicon carbide and silicone oil, wherein the concentration of the silicon carbide is 0.08% to 0.12%, and the concentration of the silicone oil is 2.5% to 3.5%.
[0076] In the present invention, the compounding of silicon carbide and silicone oil can enhance the high temperature resistance, mechanical properties and electrical conductivity of carbon fiber, and can also increase the oxidation resistance and extend the service life of carbon fiber. The concentration of silicon carbide is, for example, 0.08%, 0.09%, 0.10%, 0.11% or 0.12%.
[0077] In a preferred embodiment of the present invention, the air layer height is 3-5 mm; the coagulation bath comprises a dimethyl sulfoxide aqueous solution with a concentration of 25%-30% and a temperature of 3-5°C; the water washing process comprises alternating low-temperature water washing in a cold tank and a hot tank at 40-50°C, with a temperature difference of 2-10°C between the cold tank and the hot tank, and high-temperature water washing at 60-70°C, and the total water washing stretching multiple is 1-2 times; the steam stretching steam pressure is 1.0-1.6 MP, and the steam stretching multiple is 3.6-4.3 times.
[0078] Preferably, the low-temperature water washing includes 2 to 4 stages of cold tanks at 40 to 45°C and 2 to 4 stages of hot tanks at 45 to 50°C.
[0079] In the present invention, the cold tank is, for example, level 2, level 3 or level 4, and the temperature of the cold tank is, for example, 40°C, 41°C, 42°C, 43°C, 44°C or 45°C; the hot tank is, for example, level 2, level 3 or level 4, and the temperature of the hot tank is, for example, 45°C, 46°C, 47°C, 48°C, 49°C or 50°C.
[0080] Specifically, the cold tank and the hot tank are arranged alternately, and the arrangement of the cold tank and the hot tank is cold tank, hot tank, cold tank, hot tank, etc. For example, the arrangement of the cold tank and the hot tank in the low-temperature water washing process is:
[0081] When the cold tank is 2 levels and the hot tank is 2 levels, the cold tank and the hot tank are arranged in the order of cold tank, hot tank, cold tank, and hot tank during the low-temperature water washing process;
[0082] When the cold tank is of level 3 and the hot tank is of level 3, the cold tank and the hot tank are arranged in sequence of cold tank, hot tank, cold tank, hot tank, cold tank and hot tank during the low-temperature water washing process;
[0083] When the cold tank is of level 4 and the hot tank is of level 4, the cold tank and the hot tank are arranged in sequence of cold tank, hot tank, cold tank, hot tank, cold tank, hot tank, cold tank, hot tank during the low-temperature water washing process;
[0084] When the cold tank is of level 3 and the hot tank is of level 2, the cold tank and the hot tank are arranged in sequence of cold tank, hot tank, cold tank, hot tank, and cold tank during the low-temperature water washing process;
[0085] When the cold tank is level 4 and the hot tank is level 3, the cold tank and the hot tank are arranged in the sequence of cold tank, hot tank, cold tank, hot tank, cold tank, hot tank and cold tank during the low-temperature water washing process.
[0086] Preferably, the low-temperature water washing is alternating water washing in 3 stages of cold tanks at 40-45°C and 3 stages of hot tanks at 45-50°C.
[0087] Preferably, the low-temperature water washing is alternating water washing in three stages of 45°C cold tanks and three stages of 50°C hot tanks, that is, during the low-temperature water washing process, the spun fiber passes through a 45°C cold tank, a 50°C hot tank, a 45°C cold tank, a 50°C hot tank, a 45°C cold tank, and a 50°C hot tank in sequence.
[0088] The present invention uses a dry-jet wet spinning method to prepare polyacrylonitrile precursor, that is, after the spinning solution is ejected from the spinneret hole on the spinneret, it first passes through a section of air layer (dry section) and then enters the coagulation liquid to complete solidification. The height of the air layer can affect the morphology, diameter, structure and arrangement of the fiber. In the present invention, when the height of the air layer exceeds 5 mm, the fiber is stretched unevenly and the fiber breakage rate increases; when the height of the air layer is less than 3 mm, the degree of stretching is reduced when the fiber is ejected, the fiber diameter is relatively thick, and the internal structure of the fiber is relatively loose and irregularly arranged. The height of the air layer is between 3 and 5 mm, and the stretching is uniform, which is more conducive to improving the orientation and crystallinity of the fiber, making the fiber structure more compact and orderly.
[0089] The air layer height is, for example, 3 mm, 3.5 mm, 4 mm, 4.5 mm or 5 mm.
[0090] The water washing temperature directly affects the microstructure and final performance of the fiber. When the water temperature is lower than 40℃, the movement of the molecular chain will be restricted and the grain orientation will be insufficient, which will reduce the crystallinity of the precursor in the subsequent carbonization process, thereby reducing the mechanical properties of the carbon fiber. It will also lead to hindered crystal growth, small grain size and uneven distribution, reduced thermal stability of the precursor, low densification, and more micro defects and voids. When the temperature is higher than 70℃, the grain growth will be excessive and the orientation will be too consistent, which will increase the brittleness of the precursor and break the polymer chain, affecting the strength and elastic modulus of the carbon fiber, and the internal pores of the fiber will merge or increase, affecting the adsorption and permeability of the carbon fiber. Low-temperature water washing is carried out by alternating between a cold tank at 40~45℃ and a hot tank at 45~50℃. The precursor undergoes slight temperature fluctuations at the microscopic level, causing local movement and rearrangement of the polymer molecules, promoting the moderate orientation of the molecular chain, and the subsequent high-temperature water washing step (60~70℃) further promotes the orientation and growth of the grains, obtaining a precursor with high grain orientation and dense structure.
[0091] In the present invention, the cold tank temperature is, for example, 40°C, 41°C, 42°C, 43°C, 44°C or 45°C. The hot tank temperature is, for example, 45°C, 46°C, 47°C, 48°C, 49°C or 50°C. The high-temperature water washing temperature is, for example, 60°C, 61°C, 62°C, 63°C, 64°C, 65°C, 66°C, 67°C, 68°C, 69°C or 70°C. The total water washing drafting multiple is, for example, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9 or 2.0 times.
[0092] In a preferred embodiment of the present invention, the method for preparing polyacrylonitrile precursor is specifically as follows:
[0093] The 25~40℃ polyacrylonitrile spinning solution is transported to the spinning device through a metering pump and spun through a spinneret in an air layer with a height of 3~5mm. The filament bundle is then passed through a coagulation bath of a dimethyl sulfoxide aqueous solution with a temperature of 3~5℃ and a concentration of 25%~30% to obtain primary fibers.
[0094] Then, the spun fiber is conveyed to a washing device for washing by a driving roller. The washing device first washes the fiber alternately in 2-4 stages of a cold tank at 40-45°C and 2-4 stages of a hot tank at 45-50°C, the temperature difference between the cold and hot tanks is 2-10°C, and the cold tank and the hot tank are arranged in the order of cold tank, hot tank, cold tank, hot tank..., and then washes the fiber at a high temperature of 60-70°C, and the total washing and stretching multiple is controlled at 1-2 times.
[0095] Then, the washed fiber is blown dry by air and sent to the upper oil tank for oiling. The upper oil tank contains an aqueous solution of silicon carbide and silicone oil. The concentration of silicon carbide is 0.08%~0.12%, and the concentration of silicone oil is 2.5%~3.5%.
[0096] Then, the oiled fiber is dried at 130-170° C., and the filament bundle is sent to a steam drawing device, the steam pressure is controlled at 1.0-1.6 MPa, and the steam drawing multiple is controlled at 3.6-4.3 times to obtain polyacrylonitrile precursor.
[0097] In a preferred embodiment of the present invention, the method for carbonizing polyacrylonitrile precursor comprises:
[0098] First, the carbon fiber precursor is pre-oxidized, and then low-temperature carbonization and high-temperature carbonization are performed in sequence. Then, the surface is treated and washed, and then sizing and drying are performed to obtain ultra-high performance carbon fiber.
[0099] Preferably, the pre-oxidation temperature is 225~242°C, the pre-oxidation time is 70~90 min, and the drafting ratio is 0.92~0.94 times; the low-temperature carbonization temperature is 550~700°C, and the drafting ratio is 0.93~0.95 times; the high-temperature carbonization temperature is 1200~1800°C, and the drafting ratio is 0.95~0.97 times; the conductivity of the surface treatment liquid is 8.0~9.5ms / cm, and the drafting ratio is 0.97~0.99 times; the sizing agent concentration is 1.97%~2.03%, the sizing agent content is 0.8%~1.4%, the drying temperature is 180~220°C, and the drafting ratio is 0.995~1.005 times.
[0100] In a preferred embodiment of the present invention, the method for carbonizing polyacrylonitrile precursor specifically comprises:
[0101] First, in a pre-oxidation furnace, in an air atmosphere, the temperature is controlled to gradually increase from 225°C to 242°C, and the fiber stays in the pre-oxidation furnace for 70 to 90 minutes. The drafting multiple is 0.92 to 0.94 times to obtain pre-oxidized fiber.
[0102] Then, the pre-oxidized wire was sent to a low-temperature carbonization furnace. Under a nitrogen atmosphere, the temperature was controlled to gradually increase from 500°C to 700°C, and the drawing ratio was 0.93~0.95 times.
[0103] Then, it enters a high-temperature carbonization furnace, under a nitrogen atmosphere, at a temperature of 1200-1800°C and a drawing ratio of 0.95-0.97 times to obtain carbonized wire.
[0104] Then, the carbonized wire is surface treated in an acidic medium with a conductivity of 8.0-9.5 ms / cm and then washed with water, and the drafting ratio is 0.97-0.99 times.
[0105] Then, after sizing in a sizing agent solution with a concentration of 1.97% to 2.03%, it is dried using a steam-heated roller at a temperature of 140 to 170°C, and the sizing amount is between 0.8% and 1.4%.
[0106] Then, the sizing carbonized fiber is sequentially subjected to primary drying and secondary drying, the primary drying temperature is 180~200℃, the secondary drying temperature is 200~220℃, the drafting multiple is 0.995~1.005 times, and then it is wound into a shaft to obtain T1100 grade ultra-high performance carbon fiber.
[0107] Example 1
[0108] The specific steps for preparing ultra-high performance carbon fiber are as follows:
[0109] (1) Preparation of polyacrylonitrile spinning solution
[0110] 15 parts of acrylonitrile, 1 part of itaconic acid and 24 parts of dimethyl sulfoxide were dissolved at 40°C, filtered through a filter with a precision of 0.4 μm, and transferred to a polymerization kettle;
[0111] Then, 1.5 parts of azobisisobutyronitrile and 22.5 parts of dimethyl sulfoxide were dissolved at 40°C, passed through a 0.4 μm filter, and transferred to a polymerization kettle;
[0112] Then, 1.05 parts of 2,2'-dicyanodisulfide was added to carry out polymerization reaction.
[0113] During the polymerization reaction, the polymerization kettle was divided into multi-stage temperature control. The first stage was to control the temperature of the polymerization kettle at 55°C. After 2 hours of reaction, the temperature was raised to 65°C at a rate of 0.083°C / min for the second stage reaction. The temperature was kept for 14 hours, and the polymerization reaction conversion rate was 90.9%.
[0114] After the reaction is completed, the polymer solution is transferred to a stripping tower through a pump to remove acrylonitrile monomer, and the absolute pressure in the stripping tower is controlled to be 0.002MPa; then it is transferred to a concentration tower for concentration, and the absolute pressure in the concentration tower is controlled to be 0.0005MPa; then 8% ammonia water is added for amination for 1h, and then the polyacrylonitrile spinning solution is obtained after 3-stage filtration.
[0115] The polyacrylonitrile spinning solution has a rotational viscosity of 780P, an intrinsic viscosity of 1.8 dl / g, and a solid content of 19.5%.
[0116] (2) Preparation of polyacrylonitrile precursor
[0117] The temperature of the polyacrylonitrile spinning solution is controlled at 30°C, and is transported to the spinning device through a metering pump. The filaments are spun through a spinneret in an air layer with a height of 3.5 mm. Subsequently, the filament bundles pass through a coagulation bath of a dimethyl sulfoxide aqueous solution with a temperature of 4°C and a concentration of 28% to obtain primary fibers.
[0118] Then, the spun fiber is conveyed to a washing device by a driving roller for washing. The washing is first carried out in a cold tank at 45°C, a hot tank at 50°C, a cold tank at 45°C, a hot tank at 50°C, a cold tank at 45°C and a hot tank at 50°C in sequence for low-temperature washing, and then washed at high temperature at 65°C. The total washing and stretching multiple is controlled at 1.5 times.
[0119] Then, the washed fiber is blown dry by air and sent to an upper oil tank for oiling. The upper oil tank contains an aqueous solution of silicon carbide and silicone oil, with a silicon carbide concentration of 0.1% and a silicone oil concentration of 3.0%.
[0120] Then, the oiled fiber was dried at 150° C., and the filament bundle was sent to a steam drawing device, the steam pressure was controlled at 1.3 MPa, and the steam drawing ratio was 4.0 times, to obtain polyacrylonitrile precursor.
[0121] The polyacrylonitrile precursor has a fineness of 0.76 dtex, a single yarn strength of 7.0 cN / dtex, a single yarn elongation of 15%, a moisture content of 1.9%, a linear density unevenness of 1.2%, a modulus of 99 cN / dtex, a boiling water shrinkage of 4.0%, and an oil content of 1.0%.
[0122] (3) Carbonization of raw fibers
[0123] Firstly, in a pre-oxidation furnace, in an air atmosphere, the temperature is controlled to be gradually increased from 225°C to 242°C, and the fiber stays in the pre-oxidation furnace for 80 minutes. The drafting ratio is 0.93 times, and pre-oxidized fiber is obtained.
[0124] Then, the pre-oxidized wire was sent to a low-temperature carbonization furnace, and the temperature was gradually increased from 550°C to 700°C under a nitrogen atmosphere, with a drawing ratio of 0.94 times.
[0125] Then, it enters a high-temperature carbonization furnace, under a nitrogen atmosphere, at a temperature of 1500°C and a drawing ratio of 0.97 times to obtain carbonized wire.
[0126] Then, the carbonized fibers were surface treated in an acidic medium with a conductivity of 8.8 ms / cm and then washed with water, and the drawing ratio was 0.97 times.
[0127] Then, after sizing in a sizing agent solution with a concentration of 2%, it was dried using a steam-heated roller at a temperature of 160°C, and the sizing amount was 1.2%.
[0128] Then, the sizing carbonized fiber is sequentially dried at the primary drying temperature of 180°C and the secondary drying temperature of 210°C, with a drafting multiple of 1, and then wound into a shaft to obtain T1100 grade ultra-high performance carbon fiber.
[0129] The ultra-high performance carbon fiber obtained in Example 1 has a tensile strength of 6820 MPa, an elastic modulus of 338 GPa, an elongation at break of 2.02%, a linear density of 485 g / km, and a bulk density of 1.8 g / cm 3 , sizing agent content is 1.16%.
[0130] Example 2
[0131] The specific steps for preparing ultra-high performance carbon fiber are as follows:
[0132] (1) Preparation of polyacrylonitrile spinning solution
[0133] During the polymerization reaction, the polymerization kettle is divided into multi-stage temperature control. The first stage is to control the temperature of the polymerization kettle at 55°C. After reacting for 2 hours, the temperature is raised to 70°C at a rate of 0.083°C / min for the second stage reaction, which is kept warm for 14 hours.
[0134] The remaining steps and parameters are consistent with those in Example 1.
[0135] The polymerization reaction conversion rate was 91.0%.
[0136] The polyacrylonitrile spinning solution has a rotational viscosity of 766 P, an intrinsic viscosity of 1.84 dl / g, and a solid content of 19.13%.
[0137] (2) The steps for preparing polyacrylonitrile precursor are the same as those in Example 1.
[0138] The polyacrylonitrile precursor has a fineness of 0.74 dtex, a single yarn strength of 6.4 cN / dtex, a single yarn elongation of 14.5%, a moisture content of 2.3%, a linear density unevenness of 1.6%, a modulus of 97 cN / dtex, a boiling water shrinkage of 4.6%, and an oil content of 1.4%.
[0139] (3) The carbonization step of the raw silk is the same as that in Example 1.
[0140] The ultra-high performance carbon fiber obtained in Example 2 has a tensile strength of 6785 MPa, an elastic modulus of 339 GPa, an elongation at break of 2.0%, a linear density of 482 g / km, and a bulk density of 1.8 g / cm 3 , sizing agent content 1.2%.
[0141] Example 3
[0142] (1) Preparation of polyacrylonitrile spinning solution
[0143] During the polymerization reaction, the polymerization kettle is divided into multi-stage temperature control. The first stage is to control the temperature of the polymerization kettle at 60°C. After 2 hours of reaction, the temperature is increased to 70°C at a rate of 0.083°C / min to carry out the second stage reaction and keep warm for 14 hours.
[0144] The remaining steps and parameters are consistent with those in Example 1.
[0145] The polymerization reaction conversion rate was 91.2%.
[0146] The polyacrylonitrile spinning solution has a rotational viscosity of 746P, an intrinsic viscosity of 1.83 dl / g, and a solid content of 19.30%.
[0147] (2) The steps for preparing polyacrylonitrile precursor are the same as those in Example 1.
[0148] The polyacrylonitrile precursor has a fineness of 0.73 dtex, a single yarn strength of 7.4 cN / dtex, a single yarn elongation of 13.5%, a moisture content of 1.2%, a linear density unevenness of 1.01%, a modulus of 102 cN / dtex, a boiling water shrinkage of 2.5%, and an oil content of 0.61%.
[0149] (3) The carbonization step of the raw fiber is the same as that in Example 1.
[0150] The ultra-high performance carbon fiber obtained in Example 3 has a tensile strength of 7012 MPa, an elastic modulus of 341 GPa, an elongation at break of 2.06%, a linear density of 479 g / km, and a bulk density of 1.79 g / cm 3 , sizing agent content 1.14%.
[0151] Example 4
[0152] (1) Preparation of polyacrylonitrile spinning solution
[0153] During the polymerization reaction, the polymerization kettle is divided into multi-stage temperature control. The first stage is to control the temperature of the polymerization kettle at 65°C. After reacting for 2 hours, the temperature is raised to 70°C at a rate of 0.083°C / min for the second stage reaction, which is kept warm for 14 hours.
[0154] The remaining steps and parameters are consistent with those in Example 1.
[0155] The polymerization reaction conversion rate was 90.9%.
[0156] The polyacrylonitrile spinning solution has a rotational viscosity of 749P, an intrinsic viscosity of 1.82 dl / g, and a solid content of 19.23%.
[0157] (2) The steps for preparing polyacrylonitrile precursor are the same as those in Example 1.
[0158] The polyacrylonitrile precursor has a fineness of 0.74 dtex, a single yarn strength of 6.4 cN / dtex, a single yarn elongation of 14.1%, a moisture content of 2.25%, a linear density unevenness of 1.32%, a modulus of 95 cN / dtex, a boiling water shrinkage of 4.48%, and an oil content of 1.39%.
[0159] (3) The carbonization step of the raw fiber is the same as that in Example 1.
[0160] The ultra-high performance carbon fiber obtained in Example 4 has a tensile strength of 6794 MPa, an elastic modulus of 329 GPa, an elongation at break of 2.07%, a linear density of 483 g / km, and a bulk density of 1.80 g / cm 3 , sizing agent content 1.08%.
[0161] Example 5
[0162] (1) Preparation of polyacrylonitrile spinning solution
[0163] During the polymerization reaction, the polymerization kettle is divided into multi-stage temperature control. The first stage is to control the temperature of the polymerization kettle at 60°C. After 1 hour of reaction, the temperature is increased to 70°C at a rate of 0.083°C / min to carry out the second stage reaction, and the temperature is kept for 15 hours.
[0164] The remaining steps and parameters are consistent with those in Example 1.
[0165] The polymerization reaction conversion rate was 90.4%.
[0166] The polyacrylonitrile spinning solution has a rotational viscosity of 738P, an intrinsic viscosity of 1.84 dl / g, and a solid content of 19.32%.
[0167] (2) The steps for preparing polyacrylonitrile precursor are the same as those in Example 1.
[0168] The polyacrylonitrile precursor has a fineness of 0.76 dtex, a single yarn strength of 6.8 cN / dtex, a single yarn elongation of 14.75%, a moisture content of 1.71%, a linear density unevenness of 1.45%, a modulus of 97 cN / dtex, a boiling water shrinkage of 4.50%, and an oil content of 0.92%.
[0169] (3) The carbonization step of the raw fiber is the same as that in Example 1.
[0170] The ultra-high performance carbon fiber obtained in Example 5 has a tensile strength of 6478 MPa, an elastic modulus of 326 GPa, an elongation at break of 1.99%, a linear density of 489 g / km, and a bulk density of 1.79 g / cm 3 , sizing agent content is 1.22%.
[0171] Example 6
[0172] (1) Preparation of polyacrylonitrile spinning solution
[0173] During the polymerization reaction, the polymerization kettle was divided into multi-stage temperature control. The first stage was to control the temperature of the polymerization kettle at 60°C. After reacting for 3 hours, the temperature was raised to 70°C at a rate of 0.083°C / min for the second stage reaction, which was kept warm for 13 hours.
[0174] The remaining steps and parameters are consistent with those in Example 1.
[0175] The polymerization reaction conversion rate was 90.5%.
[0176] The polyacrylonitrile spinning solution has a rotational viscosity of 739P, an intrinsic viscosity of 1.83dl / g, and a solid content of 19.19%.
[0177] (2) The steps for preparing polyacrylonitrile precursor are the same as those in Example 1.
[0178] The polyacrylonitrile precursor has a fineness of 0.72 dtex, a single yarn strength of 6.64 cN / dtex, a single yarn elongation of 14.76%, a moisture content of 2.81%, a linear density unevenness of 1.64%, a modulus of 93 cN / dtex, a boiling water shrinkage of 4.08%, and an oil content of 1.33%.
[0179] (3) The carbonization step of the raw fiber is the same as that in Example 1.
[0180] The ultra-high performance carbon fiber obtained in Example 6 has a tensile strength of 6921 MPa, an elastic modulus of 325 GPa, an elongation at break of 2.13%, a linear density of 486 g / km, and a bulk density of 1.80 g / cm 3 , sizing agent content 0.97%.
[0181] Example 7
[0182] (1) Preparation of polyacrylonitrile spinning solution
[0183] During the polymerization reaction, the polymerization kettle is divided into multi-stage temperature control. The first stage is to control the temperature of the polymerization kettle at 60°C. After 2 hours of reaction, the temperature is increased to 70°C at a rate of 0.05°C / min for the second stage reaction, and the temperature is kept for 14 hours.
[0184] The remaining steps and parameters are consistent with those in Example 1.
[0185] The polymerization reaction conversion rate was 90.2%.
[0186] The polyacrylonitrile spinning solution has a rotational viscosity of 732P, an intrinsic viscosity of 1.87 dl / g, and a solid content of 19.32%.
[0187] (2) The steps for preparing polyacrylonitrile precursor are the same as those in Example 1.
[0188] The polyacrylonitrile precursor has a fineness of 0.70 dtex, a single yarn strength of 6.85 cN / dtex, a single yarn elongation of 14.55%, a moisture content of 1.82%, a linear density unevenness of 1.45%, a modulus of 97 cN / dtex, a boiling water shrinkage of 3.52%, and an oil content of 1.03%.
[0189] (3) The carbonization step of the raw silk is the same as that in Example 1.
[0190] The ultra-high performance carbon fiber obtained in Example 7 has a tensile strength of 6689 MPa, an elastic modulus of 329 GPa, an elongation at break of 2.03%, a linear density of 485 g / km, and a bulk density of 1.79 g / cm 3 , sizing agent content 1.05%.
[0191] Example 8
[0192] (1) Preparation of polyacrylonitrile spinning solution
[0193] During the polymerization reaction, the polymerization kettle is divided into multi-stage temperature control. The first stage is to control the temperature of the polymerization kettle at 60°C. After reacting for 2 hours, the temperature is increased to 70°C at a rate of 0.15°C / min for the second stage reaction, and the temperature is kept for 14 hours.
[0194] The remaining steps and parameters are consistent with those in Example 1.
[0195] The polymerization reaction conversion rate was 90.1%.
[0196] The polyacrylonitrile spinning solution has a rotational viscosity of 730P, an intrinsic viscosity of 1.90 dl / g, and a solid content of 19.30%.
[0197] (2) The steps for preparing polyacrylonitrile precursor are the same as those in Example 1.
[0198] The polyacrylonitrile precursor has a fineness of 0.68 dtex, a single yarn strength of 6.74 cN / dtex, a single yarn elongation of 13.82%, a moisture content of 1.53%, a linear density unevenness of 1.50%, a modulus of 90 cN / dtex, a boiling water shrinkage of 3.64%, and an oil content of 1.28%.
[0199] (3) The carbonization step of the raw silk is the same as that in Example 1.
[0200] The ultra-high performance carbon fiber obtained in Example 8 has a tensile strength of 6622 MPa, an elastic modulus of 330 GPa, an elongation at break of 2.01%, a linear density of 490 g / km, and a bulk density of 1.80 g / cm 3 , sizing agent content 1.00%.
[0201] Comparative Example 1
[0202] (1) Preparation of polyacrylonitrile spinning solution
[0203] During the polymerization reaction, the polymerization kettle is divided into multi-stage temperature control. The first stage is to control the temperature of the polymerization kettle at 50°C. After reacting for 2 hours, the temperature is raised to 80°C at a rate of 0.083°C / min to carry out the second stage reaction, which is kept warm for 14 hours.
[0204] The remaining steps and parameters are consistent with those in Example 1.
[0205] The polymerization reaction conversion rate was 84.4%.
[0206] The polyacrylonitrile spinning solution has a rotational viscosity of 728P, an intrinsic viscosity of 1.88dl / g, and a solid content of 19.18%.
[0207] (2) The steps for preparing polyacrylonitrile precursor are the same as those in Example 1.
[0208] The polyacrylonitrile precursor has a fineness of 0.71 dtex, a single yarn strength of 6.86 cN / dtex, a single yarn elongation of 14.99%, a moisture content of 2.98%, a linear density unevenness of 1.52%, a modulus of 90 cN / dtex, a boiling water shrinkage of 4.86%, and an oil content of 1.49%.
[0209] (3) The carbonization step of the raw fiber is the same as that in Example 1.
[0210] The ultra-high performance carbon fiber obtained in Comparative Example 1 has a tensile strength of 6582 MPa, an elastic modulus of 336 GPa, an elongation at break of 1.96%, a linear density of 495 g / km, and a bulk density of 1.81 g / cm 3 , sizing agent content 1.20%.
[0211] Comparative Example 2
[0212] (1) Preparation of polyacrylonitrile spinning solution
[0213] During the polymerization reaction, the polymerization kettle is divided into multi-stage temperature control. The first stage is to control the temperature of the polymerization kettle at 45°C. After reacting for 2 hours, the temperature is raised to 70°C at a rate of 0.083°C / min to carry out the second stage reaction, which is kept warm for 14 hours.
[0214] The remaining steps and parameters are consistent with those in Example 1.
[0215] The polymerization reaction conversion rate was 89.2%.
[0216] The polyacrylonitrile spinning solution has a rotational viscosity of 745P, an intrinsic viscosity of 1.89 dl / g, and a solid content of 18.92%.
[0217] (2) The steps for preparing polyacrylonitrile precursor are the same as those in Example 1.
[0218] The polyacrylonitrile precursor has a fineness of 0.73 dtex, a single yarn strength of 6.84 cN / dtex, a single yarn elongation of 15.85%, a moisture content of 2.78%, a linear density unevenness of 1.40%, a modulus of 91 cN / dtex, a boiling water shrinkage of 4.80%, and an oil content of 1.52%.
[0219] (3) The carbonization step of the raw fiber is the same as that in Example 1.
[0220] The ultra-high performance carbon fiber obtained in Comparative Example 2 has a tensile strength of 6420 MPa, an elastic modulus of 334 GPa, an elongation at break of 1.92%, a linear density of 490 g / km, and a bulk density of 1.81 g / cm 3 , sizing agent content 1.19%.
[0221] Comparative Example 3
[0222] (1) Preparation of polyacrylonitrile spinning solution
[0223] During the polymerization reaction, the polymerization kettle is divided into multi-stage temperature control. The first stage is to control the temperature of the polymerization kettle at 55°C. After reacting for 4 hours, the temperature is raised to 70°C at a rate of 0.083°C / min for the second stage reaction, which is kept warm for 10 hours.
[0224] The remaining steps and parameters are consistent with those in Example 1.
[0225] The polymerization reaction conversion rate was 89.4%.
[0226] The polyacrylonitrile spinning solution has a rotational viscosity of 750 P, an intrinsic viscosity of 1.87 dl / g, and a solid content of 19.04%.
[0227] (2) The steps for preparing polyacrylonitrile precursor are the same as those in Example 1.
[0228] The polyacrylonitrile precursor has a fineness of 0.74 dtex, a single yarn strength of 6.72 cN / dtex, a single yarn elongation of 13.76%, a moisture content of 2.06%, a linear density unevenness of 1.29%, a modulus of 90 cN / dtex, a boiling water shrinkage of 4.72%, and an oil content of 1.08%.
[0229] (3) The carbonization step of the raw fiber is the same as that in Example 1.
[0230] The ultra-high performance carbon fiber obtained in Comparative Example 3 has a tensile strength of 6607 MPa, an elastic modulus of 339 GPa, an elongation at break of 1.95%, a linear density of 479 g / km, and a bulk density of 1.79 g / cm 3 , sizing agent content 1.08%.
[0231] Comparative Example 4
[0232] (1) Preparation of polyacrylonitrile spinning solution
[0233] The polymerization temperature was 70°C and the reaction time was 16 h.
[0234] The remaining steps and parameters are consistent with those in Example 1.
[0235] The polymerization reaction conversion rate was 86.2%.
[0236] The polyacrylonitrile spinning solution has a rotational viscosity of 733 P, an intrinsic viscosity of 1.82 dl / g, and a solid content of 19.08%.
[0237] (2) The steps for preparing polyacrylonitrile precursor are the same as those in Example 1.
[0238] The polyacrylonitrile precursor has a fineness of 0.76 dtex, a single yarn strength of 5.89 cN / dtex, a single yarn elongation of 14.20%, a moisture content of 3.01%, a linear density unevenness of 1.54%, a modulus of 87 cN / dtex, a boiling water shrinkage of 5%, and an oil content of 1.63%.
[0239] (3) The carbonization step of the raw fiber is the same as that in Example 1.
[0240] The ultra-high performance carbon fiber obtained in Comparative Example 4 has a tensile strength of 6460 MPa, an elastic modulus of 342 GPa, an elongation at break of 1.88%, a linear density of 502 g / km, and a bulk density of 1.82 g / cm 3 , sizing agent content 1.29%.
[0241] Comparative Example 5
[0242] (1) Preparation of polyacrylonitrile spinning solution
[0243] The polymerization temperature was 60°C and the reaction time was 16 h.
[0244] The remaining steps and parameters are consistent with those in Example 1.
[0245] The polymerization reaction conversion rate was 84.2%.
[0246] The polyacrylonitrile spinning solution has a rotational viscosity of 755 P, an intrinsic viscosity of 1.85 dl / g, and a solid content of 19.27%.
[0247] (2) The steps for preparing polyacrylonitrile precursor are the same as those in Example 1.
[0248] The polyacrylonitrile precursor has a fineness of 0.79 dtex, a single yarn strength of 6.02 cN / dtex, a single yarn elongation of 14.12%, a moisture content of 3.41%, a linear density unevenness of 1.83%, a modulus of 80 cN / dtex, a boiling water shrinkage of 5%, and an oil content of 1.79%.
[0249] (3) The carbonization step of the raw fiber is the same as that in Example 1.
[0250] The ultra-high performance carbon fiber obtained in Comparative Example 5 has a tensile strength of 6379 MPa, an elastic modulus of 340 GPa, an elongation at break of 1.88%, a linear density of 500 g / km, and a bulk density of 1.82 g / cm 3 , sizing agent content is 1.21%.
[0251] Comparative Example 6
[0252] (1) Preparation of polyacrylonitrile spinning solution
[0253] During the polymerization reaction, the polymerization kettle is divided into multi-stage temperature control. The first stage is to control the temperature of the polymerization kettle at 60°C. After 2 hours of reaction, the temperature is increased to 70°C at a rate of 0.2°C / min for the second stage reaction, and the temperature is kept for 14 hours.
[0254] The remaining steps and parameters are consistent with those in Example 1.
[0255] The polymerization reaction conversion rate was 85.7%.
[0256] The polyacrylonitrile spinning solution has a rotational viscosity of 748 P, an intrinsic viscosity of 1.84 dl / g, and a solid content of 19.16%.
[0257] (2) The steps for preparing polyacrylonitrile precursor are the same as those in Example 1.
[0258] The polyacrylonitrile precursor has a fineness of 0.77 dtex, a single yarn strength of 5.93 cN / dtex, a single yarn elongation of 13.96%, a moisture content of 2.57%, a linear density unevenness of 1.58%, a modulus of 84 cN / dtex, a boiling water shrinkage of 4.99%, and an oil content of 1.66%.
[0259] (3) The carbonization step of the raw fiber is the same as that in Example 1.
[0260] The ultra-high performance carbon fiber obtained in Comparative Example 6 has a tensile strength of 6532 MPa, an elastic modulus of 340 GPa, an elongation at break of 1.82%, a linear density of 499 g / km, and a bulk density of 1.81 g / cm 3 , sizing agent content 1.20%.
[0261] The above description is only a preferred embodiment of the present invention and an explanation of the technical principles used. Those skilled in the art should understand that the scope of the invention involved in the present invention is not limited to the technical solution formed by a specific combination of the above technical features, but should also cover other technical solutions formed by any combination of the above technical features or their equivalent features without departing from the inventive concept. For example, the above features are replaced with the technical features with similar functions disclosed in the present invention (but not limited to) by each other.
Claims
1. A method for preparing ultra-high performance carbon fiber, characterized in that: The preparation method comprises: Firstly, a polyacrylonitrile spinning solution is prepared, then a polyacrylonitrile precursor is prepared, and then the polyacrylonitrile precursor is carbonized to obtain carbon fiber; The preparation method of the polyacrylonitrile spinning solution comprises: After acrylonitrile, itaconic acid, solvent and initiator are mixed, molecular weight regulator is added, and the mixture is first reacted at 55-65°C for 1-3 hours in the first stage, and then heated to 65-75°C for 13-15 hours in the second stage at a heating rate of 0.05-0.15°C / min; Then the monomer is removed, and the polyacrylonitrile spinning solution is obtained after concentration, ammoniation and filtration; The heating rate from the first stage to the second stage is 0.083℃ / min, and the polymerization reaction conversion rate is 91.2%. On the basis of the maximum conversion rate, a narrow molecular weight distribution is obtained, the fiber structure is uniform and regular, and the molecular chain breakage damage is reduced. The tensile strength of the ultra-high performance carbon fiber is 7012 MPa, the elastic modulus is 341 GPa, the elongation at break is 2.06%, the linear density is 479g / km, the bulk density is 1.79g / cm3, and the sizing agent content is 1.14%.
2. The preparation method according to claim 1, characterized in that The polyacrylonitrile spinning solution comprises the following raw materials in parts by weight: Acrylonitrile 12~19 parts Itaconic acid 0.5~1.5 parts 30~60 parts of solvent 0.6~1.9 parts of initiator, and Molecular weight regulator 1~1.5 parts.
3. The preparation method according to claim 1, characterized in that: The method for preparing the polyacrylonitrile spinning solution further comprises: First, acrylonitrile and itaconic acid are dissolved in the first solvent, filtered, and then transferred to a polymerization kettle, wherein the mass ratio of acrylonitrile to itaconic acid is 10-15:1; the mass ratio of acrylonitrile and itaconic acid to the first solvent is 1:1-2; Then, the initiator is dissolved in the second solvent, filtered, and transferred to a polymerization kettle, wherein the mass ratio of the initiator to the second solvent is 1:14-15; Then, a molecular weight regulator was added to start the polymerization reaction, wherein the mass ratio of the molecular weight regulator to acrylonitrile was 7:
100.
4. The preparation method according to claim 2, characterized in that: The solvent includes dimethyl sulfoxide, the initiator includes azobisisobutyronitrile, and the molecular weight regulator includes one or more of 2,2'-dicyandisulfide, succinyl diamide, ethylene glycol formate, or tris(2-benzimidazolyl)silane.
5. The preparation method according to claim 1, characterized in that: The monomer removal is carried out in a monomer removal tower, and the pressure of the monomer removal tower is 0.001-0.002 MPa; the concentration is carried out in a concentration tower, and the pressure of the concentration tower is 0.0004-0.00065 MPa.
6. The preparation method according to any one of claims 1 to 5, characterized in that: The polyacrylonitrile spinning solution has a temperature of 25-40° C., a rotational viscosity of 730-780 P, an intrinsic viscosity of 1.8-1.9 dL / g, and a solid content of 18.9%-19.5%.
7. The preparation method according to claim 1, characterized in that: The method for preparing polyacrylonitrile precursor comprises: After the spinning solution is spun by the spinneret, it first passes through an air layer and then passes through a coagulation bath to form primary fibers. The primary fibers are then washed, oiled, dried, and steam-stretched to obtain polyacrylonitrile precursor fibers. The oiling step is carried out in an aqueous solution of silicon carbide and silicone oil, wherein the concentration of the silicon carbide is 0.08% to 0.12% of the aqueous solution, and the concentration of the silicone oil is 2.5% to 3.5% of the aqueous solution.
8. The preparation method according to claim 7, characterized in that: The air layer height is 3~5mm; the coagulation bath is a dimethyl sulfoxide aqueous solution with a concentration of 25%~30% and a temperature of 3~5°C; the water washing process is alternating low-temperature water washing in a cold tank and a hot tank at 40~50°C, the temperature difference between the cold tank and the hot tank is 2~10°C, and high-temperature water washing at 60~70°C, and the total water washing stretching multiple is 1~2 times; the steam stretching steam pressure is 1.0~1.6MP, and the steam stretching multiple is 3.6~4.3 times.
9. The preparation method according to claim 1, characterized in that: The method of carbonizing polyacrylonitrile precursor includes: First, the carbon fiber precursor is pre-oxidized, then subjected to low-temperature carbonization and high-temperature carbonization in sequence, then surface treated and washed, and then sized and dried to obtain ultra-high performance carbon fiber; The pre-oxidation temperature is 225-242° C., the pre-oxidation time is 70-90 min, and the drafting ratio is 0.92-0.94 times; the low-temperature carbonization temperature is 550-700° C., and the drafting ratio is 0.93-0.95 times; the high-temperature carbonization temperature is 1200-1800° C., and the drafting ratio is 0.95-0.97 times. The conductivity of the surface treatment liquid is 8.0-9.5 ms / cm, and the drafting ratio is 0.97-0.99 times. The sizing agent concentration is 1.97%-2.03%, the sizing agent content is 0.8%-1.4%, the drying temperature is 180-220° C., and the drafting ratio is 0.995-1.005 times.
Citation Information
Patent Citations
Preparation method of high-solid-content polyacrylonitrile-based carbon fiber spinning solution with controllable viscosity
CN104562222A
High-strength high-modulus carbon fiber and preparation method thereof
CN117403351A
Cited By
Method for determining pre-oxidation process parameters of polyacrylonitrile-based carbon fibers
CN120989768A
Method for determining pre-oxidation process parameters of polyacrylonitrile-based carbon fibers
CN120989768B